Synergistic effect of graphene oxide/halloysite in anticorrosion performance and flame retardancy properties of epoxy nanocomposite coating - Siti Maznah, Kabeb; Azman, Hassan; Zurina, Mohamad; Zalilah, Sharer; Munirah, Mokhtar; Faiz, Ahmad (The Italian Association of Chemical Engineering-AIDIC, 2020)
Synergistic effect composed of graphene oxide (GO) and halloysite (HNT) to serve as a promising anticorrosion performance and to enhance flame retardant (FR) properties of epoxy nanocomposite coating (NC) is studied. Using an epoxy as the matrix, GO/epoxy, HNT/epoxy, and hybrid GO/HNT/epoxy samples are prepared and the performance is characterized. The hybridization of GO and HNT leads to improve the barrier properties with EGO0.6H0.3 hybrid sample endows optimum synergistic effect. This is due to the improved state of nanofiller dispersion as well as better interfacial adhesion between the nanofillers and matrix which was confirmed by Transmission Electron microscopy (TEM) images. The Salt Spray test (SST) results corresponding to these effects reaffirmed that the corrosion resistance of the hybrid coatings improved with increasing the inorganic phase content. The thermal stability and flammability properties were investigated using Thermogravimetric Analysis (TGA) and Limiting Oxygen Index (LOI). The results of the LOI test showed that the addition of nanofillers marginally increases the LOI value of the epoxy NC. These results manifestly demonstrated that the formation of an efficient hybrid network slightly enhanced the coating performance through the synergy effect of hybrid nanofillers.